Rod-Type Ce/Cr/Nd : YAG Ceramic Lasers with White-Light Pump Source - T. Saiki; T. Iwashita; J. Sakamoto; T. Hayashi; T. Nakamachi; Y. Fujimoto; Y. Iida; M. Nakatsuka (International Journal of Optics)
Ceramic is promising for use as a solid-laser material pumped with solar or lamp light. We developed a Cr3+ ion doped Nd : YAG ceramic laser that converts white light into near-infrared laser light more efficiently. Investigation of its optical properties has revealed that large gain can be realized with excitation power that is one order of magnitude less than that in the case of Nd : YAG. Ce3+ ion doping also makes it possible to utilize the excitation light components with wavelengths of 350 nm or less, preventing generation of color centers. A rod-type Ce3+/Cr3+/Nd : YAG ceramic pumped by white light such as solar light or flash lamp light was developed. Fluorescence lifetime of ceramic was measured. Laser oscillations at free running mode were observed. Also, numerical calculation for output laser power and gain at lasing threshold was performed. Fluorescence lifetime increased as temperature rose, which was observed in Cr/Nd : YAG ceramic. This increase suggests the existence of a cross-relaxation effect. Maximum output laser energy of 73 mJ with the peak power of 330 W was obtained. Obtained output laser energy was around twice more than that in case of Cr3+/Nd : YAG ceramic with the same Nd and Cr ion concentration.